UNDERSTANDING THE PATHWAYS TO YOUTH INVOLVEMENT IN THE JUVENILE JUSTICE SYSTEM: A LONGITUDINAL INVESTIGATION OF POOR, INNER-CITY AFRICAN AMERICAN ADOLESCENTS - Harris, Charlene (2015)
It is widely recognized that African American youth are disproportionately represented in the juvenile justice system in comparison to other ethnic/racial groups, and this has generated a large body of research into the etiology and prevention of crime in this population. Although there has been considerable research attention to identifying and reducing the disproportionate contact among African American youth within the juvenile justice system, it is still unclear what factors contribute to their involvement in the criminal justice system. Accordingly, the dissertation tests whether self-reports of behaviors in early adolescence are predictive official offending behaviors in late adolescence, as measured by juvenile court data in a sample of poor, inner-city African American youth. To do so, the study uses data from a multiple-cohort longitudinal sample (N = 11,838, 49% females) of poor, inner-city African American youth, part of the Mobile Youth Survey (MYS). The dissertation consists of three related studies, which are presented in three parts. The first study investigated the consistency of youth self-reports in predicting youth involvement in the juvenile justice system, as measured by juvenile court records. Specifically, this study focused on the substantive and methodological question of whether youth self-report of violence and violent victimization during early adolescence (ages 10-12 years) longitudinally foretold official offending, based on juvenile court records. The results showed that self-reported behaviors (violent victimization and violence perpetration) were predictive of subsequent juvenile offending behaviors as measured by official records. Interestingly, self-reported weapon carrying in early adolescence was not indicative of subsequent official violent offending in adolescents at age 18. Alternatively, the effects of violence perpetration, violent victimization, and weapon carrying appeared unrelated to status offenses. The second study tested the strength of the school to prison pipeline in the African American youth sample. Recent research as well as a number of educational as well as criminal justice policies and practices in the United States (e.g., zero-tolerance policies and school disciplinary codes) provided evidence that minority youth, in particular, are “pushed from the school and into prison.” Subsequently, this second study evaluated the strength of the school to prison pipeline framework, by testing whether the predictive strength of school disciplinary actions (expulsion and suspension) in early adolescence (ages 10-11) predicted subsequent offending at age 18, as indicated by juvenile court records; also testing the potentially ameliorating or exacerbating effects of the family environment (monitoring and permissiveness) on the link between school offenses and juvenile court records (moderation effects).The findings showed that school disciplinary actions (expulsion and suspension) in early adolescence was indicative of juvenile court referrals in late adolescence. Similarly, parental permissiveness was predictive of juvenile court referrals. Interestingly, the results provided no evidence to support the moderating effects of both parenting measures (monitoring and permissiveness) on the link between school disciplinary actions and juvenile offending in the sample. Finally, the third study examined the direct and indirect effects of self-reported behaviors on subsequent official offending. In particular, the study tested whether explosive anger among youth in early adolescence (age 10) predicted juvenile court contact, measured by juvenile court referrals and two measures of offending, measured by status offenses and, violent offenses in late adolescence (age 18). Direct effects of explosive anger on juvenile court referrals and offending behaviors were not significant. However, indirect effects showed that the effect of explosive anger on juvenile justice contact (measured by juvenile court referrals) through violent victimization, violence perpetration, and, weapon carrying was significant. Furthermore, the indirect effect of explosive anger on violent offenses through weapon carrying was significant in the model. These findings provided support for the mediating effects of explosive anger on juvenile justice contact through violent victimization, violence perpetration, and weapon carrying, as well as the mediating effects of explosive anger on violent offenses through weapon carrying. No indirect effects of explosive anger were found for status offenses